Green tea consumption and cerebral white matter lesions in community-dwelling older adults without dementia - Shutaro Shibata; Moeko Noguchi-Shinohara; Ayano Shima; Taro Ozaki; Yuta Usui; Yasuyuki Taki; Kazuhiro Uchida; Takanori Honda; Jun Hata; Tomoyuki Ohara; Tatsuya Mikami; Tetsuya Maeda; et al. (npj Science of Food)
Abstract This study investigated the association between green tea or coffee consumption with cerebral white matter lesions and hippocampal and total brain volumes among 8766 community-dwelling participants recruited from the Japan Prospective Studies Collaboration for Aging and Dementia between 2016 and 2018. A Food Frequency Questionnaire was used to assess green tea and coffee consumption, whereas brain magnetic resonance imaging was performed to assess cerebral white matter lesions, hippocampal volume, and total brain volume. Multivariable-adjusted analysis revealed significant correlations between fewer cerebral white matter lesions and higher green tea consumption, whereas no significant differences were found between green tea consumption and hippocampal or total brain volume. Regarding coffee consumption, no significant differences were observed in cerebral white matter lesions or hippocampal or total brain volumes. Hence, higher green tea consumption was associated with fewer cerebral white matter lesions, suggesting that it may be useful in preventing dementia.